PROSES PENYELESAIAN KASUS PENCURIAN BUAH KELAPA SAWIT DI WILAYAH HUKUM KEPOLISIAN SEKTOR KONGBENG - Matias Matias (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT Theft is an act of crime, which greatly disturbs the comfort of the community. For that we need a consistent action that can uphold the law, so that harmony is established. the underlying factor for the crime of stealing oil palm fruit in Kongbeng District is due to the lack of income of the perpetrators of the theft (economic factors of the perpetrators is low), because of the lack of education level of the perpetrators of the theft, and because the perpetrators of the theft do not have a permanent job. This is what influences or lies behind the crime of stealing oil palm fruit. law enforcement officials who are authorized in handling cases of theft of oil palm fruit to be serious in their handling and involve community participation in order to create order and mutual security. Keywords: Theft. Palm oil